Peningkatan Kompetensi Guru Dalam Mengembangkan Media Pembelajaran Berbasis Animasi - Heni Pratiwi; Siti Rochmiyati (Departement of Mathematics Education, 2023)
The use of media is very important for teachers in learning. However, the lessons given so far seem textual and boring. This is due to the lack of knowledge and ability of teachers in making interesting variations of learning media. For this reason, Powtoon animation media is needed, so that learning becomes more meaningful and students feel enthusiastic in participating in learning. The purpose of this school action research is to describe the improvement of teacher competence in developing Powtoon animation-based learning media through workshop activities. This research uses a school action research method with two cycles. The subjects are teachers of SMP Negeri 2 Yogyakarta with 33 teachers. Collecting data with questionnaires, assignments, and observations. Based on the analysis results, this workshop includes two cycles with four stages each (Planning, Implementation, Monitoring and Evaluation, Reflection). Based on the results of the first cycle, the teacher's competence in making Powtoon animation is 70.24% including the Enough category so that in developing new learning media products 41.67% are collected and in the Less category. Next, Cycle II was carried out with mentoring strategies by researchers in collaboration with colleagues. From cycle II data, the competence of teachers in making Powtoon animation is 98.02%, including the Very Good category, and the product results have reached 100% and the Very Good category. This shows an increase in teacher competence in developing Powtoon animation-based learning media.